Diamond Open Access: Researcher’s Best Friend or just a Distant Relative? - Savolainen, Eeva; Seitsonen, Katri (Septentrio Conference Series, 2023)
The costs of Open Access publishing increase year by year (e.g. Zhang et al. 2022). Diamond Open Access (OA), in which journals and platforms do not charge fees to either authors or readers, has been hoped to provide solutions for the current situation. Also, the Council of the EU highlights the importance of Diamond OA in the recent Council Conclusions (8827/23). Various incentives, such as Action Plan for Diamond Open Access, DIAMAS and Craft-OA are established to support the development of Diamond OA. However, do researchers really use Diamond OA publication venues? Is Diamond OA a researcher’s best friend or just a rarely met distant relative? Both international (Bosman et al. 2021) and national level (Frantsvåg 2022) studies have been conducted in relation with Diamond OA. This poster views the phenomenon on a local level by illustrating Diamond OA publishing at the Finnish Aalto University in 2018–2022. Aalto University consists of six schools: School of Arts, Design and Architecture, School of Business, School of Chemical Engineering, School of Electrical Engineering, School of Engineering and School of Science. Aalto Current Research Information System, ACRIS contains the comprehensive publication data of university’s researchers. Information on Diamond OA journals was added to ACRIS journal records in the spring 2023. We identified Diamond OA journals in ACRIS by using Directory of Open Access Journals and journals’ web pages. This information in relation with publication data will form the basis for our analysis. We recognize that information on Diamond OA is incomplete and our results only indicative, since only a third of diamond OA journals are indexed in DOAJ (Bosman et al. 2021). The poster seeks to illustrate the usage of Diamond OA channels from various aspects. How has Diamond OA publishing evolved over the years? Which Diamond OA journals and publishers are the most popular? What are the differences between schools? What is the share of Diamond OA compared with other Open Access types and how has the usage of different Open Access paths evolved?